Strategi Pemasaran Global di Pasar Indonesia - Anni Zuhro Syafrida Hasibuan; Nuri Aslami (Intitut Agama Islam Nasional Laa Roiba Bogor, 2021)
This review expects to get a worldwide advertising system in the Indonesian market for Indonesian organizations. The examination strategy utilized is expressive investigation technique. The blend of key showcasing variation and standard promoting system is worldwide advertising that is as per economic situations in Indonesia. It tends to be perceived that globalization is another test for organizations in executing advertising systems. Because of globalization, organizations are needed to rival elite organizations that have huge capital and more excellent items. In Indonesia, it turns into the objective market for worldwide organizations to expand their benefits, while Indonesian organizations lose in the opposition. Keywords: global marketing strategy, globalization